Aspectos hormonais e imunológicos associados às formas graves e complicações da hanseníase - Oliveira, Daniela Teles de (2017)
Leprosy is a chronic, infectious-contagious disease caused by the Mycobacterium leprae bacillus. This is transmitted by airway and infects phagocytic cells of the skin and the Schwann cells of the peripheral nerves. Despite clinical treatment, patients may present with inflammatory complications such as leprosy reactions and lesions on peripheral nerves which may progress to physical disability. The disease may present different profiles of immune responses that are related to its clinical manifestations. Although it is known about the immune response in leprosy and the influence of hormones in the evolution of infections, there is still no understanding to generate markers that can define the most serious clinical forms and inflammatory complications of the disease. Therefore, this work aimed to identify immunological and hormonal aspects associated with the clinical presentation and complications of leprosy. The methodology included a cross-sectional study comparing groups based on the collection of clinical data and serum markers (immunological and hormonal) of healthy contact controls and patients with leprosy. In addition, a cohort study was carried out with monthly follow up and up to one year after clinical discharge in order to evaluate the occurrence of reactional episodes and/or physical disability. Serum levels of hormones (adrenocorticotrophic- ACTH, cortisol, Insulin-like growth factor type 1-IGF-1 and testosterone) and cytokines (INF-ɣ, IL-12p70, IL-17A, IL1-β, IL-10 and TNF-ɣ was related to clinical forms (indeterminate-IL, tuberculoid-TT, boderline-BL and lepromatous- LL), operational classification (paucibacillary-PB and multibacillary-MB), presence of reactional episodes and physical disability. There was a higher proportion of MB men (54.3%). MB patients also had a higher frequency of reaction episodes (44.4%) and physical disability (76.5%) when compared to patients with PB. As regards the presence of circulating hormones, high levels of ACTH were found in MB (24.2 ±13.1 ng/ml, p= 0.002) and PB (23.5 ± 14.9 ng/ml, p = 0.007) when compared whit controls (11.9 ± 12.3 ng/ml). High levels of cortisol were also detected in TT patients (12.1 ± 4.7 μg/dl) compared to controls (8.4 ± 2.7 μg/dl, p = 0.003), BL (9.02 ± 4 , 8 μg/dL, p = 0.004) and LL (8.9 ± 2.7 μg/dL, p = 0.03). Patients who had leprosy before treatment had lower levels of ACTH (19.7 ± 10.3 ng/ml) and cortisol (8.5±3.9 ng/ml; p= 0.04) when compared with the patients without reaction. A positive correlation was observed when correlating ACTH and cortisol between the hormones (CI: 0.35-0.65, r= 0.52, p <0.0001). Higher IGF-1 levels were obtained in IL patients (6.5 ± 6.4 ng/ml) than in the other forms (TT 3.03 ± 3.5 ng/ml; BL 3.1 ± 4.5 ng/ml; LL 3.6 ± 2.5 ng/ml). Patients with physical disabilities (grades 1 and 2) have lower levels of IGF-1 (2.8 ± 1.6 ng/ml) compared to those without this limitation (grade 0: 4.5 ± 2,7 ng/ml, p= 0.007). High testosterone levels were found in men over 50 years of age and MB (6.58 ± 3.2 ng/ml) when compared to PB men (4.21 ± 2.3 ng/ml) and controls (4.26 ± 0,8 ng/ml). Regarding the evaluation of immunological markers, all the cytokines evaluated were increased in the patients, in comparison to the controls, highlighting INF-ɣ (79.02 ± 26.9 pg/ml), IL-10 (156.4 ± 53 pg/ml) and TNF-α (463.3±160.6 pg/ml) that were elevated in the LL forms. Regarding IL-17A, patients with TT presented higher levels (49.2±10.5 pg/ml) when compared to patients with LL (40.7 ± 4.6 pg/ml). IL1-β was elevated in IL forms (62.9 ± 16.3 pg/ml) when compared to more severe forms of the disease and controls. Finally, the increase in INF-ɣ (97.1 ± 44.5 pg/ml, p= 0.02) and TNF-α (407.3 ± 82.08 pg/ml, p= 0.04) was related in MB patients to the occurrence of reaction episode. The latter was also higher in patients with physical disability (354.3 ± 92.2 pg/ml, p= 0.04). The hormonal and immunological markers support the hypothesis that the interaction between leprosy and the neuroendocrine and immunological systems play an important role in the natural course of M. leprae infection. Reduced concentrations of cortisol and IGF-1, high testosterone concentrations related to the worst clinical outcome suggest that these hormones are important modulators of the inflammatory episode and supports future therapeutical studies as well as the attempt of prophylactic treatment. In addition, IL-17 and IL-1β cytokines act to control bacillus multiplication. The cytokines IFN-ɣ and TNF-α were associated with the presence of a reaction suggesting a deleterious effect on the lesion.